APLIKASI BIOKOMPOS “TRICHOSUBUR PROTECT” DAN PENGARUHNYA TERHADAP BERAT UMBI BAWANG MERAH (Allium ascalonicum L) VARIETAS LEMBAH PALU - Nurzakia Nurzakia; Umrah Umrah; Abdul Rahim Thaha (Biocelebes, 2017)
The research of the test of bio-compost effectiveness “Trichosubur Protect” to the red onion varieties growth (Allium ascalonicum L) in Palu valley has been conducted since from November 2015- to merch 2016. It was located in Hortus Botanicus land area (Botanical Park) departemen of Biology, Mathematics and Natural Sciences Faculty of Tadulako University. This research was designed through complete randomized design that consisted of 5 treatments and 3 repetitions. The treatmen was planting media (19 kg soil mix + 1 kg paddy husk) through bio-compost application “Trichosubur Protect” : P1 (planting media + 10 g “Trichosubur Protect”), P2 (planting media + 20 g “Trichosubur Protect”), P3 (planting media + 30 g “Trichosubur Protect”), P4 (planting media + 40 g “Trichosubur Protect”).The Parameters include the observation of leaf weight at harvest (g), the weight of tubers at harvest (g), root weight at harvest (g). The results showed that the application biokompos "Trichosubur Protect" effective (significant) to the weight of onion bulbs (Allium ascalonicum L) varieties Palu valley during harvest. P4 is the best treatment compared with other treatments, is seen in the average weight of leaves at harvest (7.21 g), the weight of tubers at harvest (18.73 g), root weight at harvest (0.87 g).